Composite Materials in Design Processes - Minak, Giangiacomo; Minak, Giangiacomo (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The use of composite materials in the design process allows one to tailer a component$1 (Bs mechanical properties, thus reducing its overall weight. On the one hand, the possible combinations of matrices, reinforcements, and technologies provides more options to the designer. On the other hand, it increases the fields that need to be investigated in order to obtain all the information requested for a safe design. This Applied Sciences Special Issue, (3z(BComposite Materials in Design Processes(3y(B, collects recent advances in the design methods for components made of composites and composite material properties at a laminate level or using a multi-scale approach.s
English
Keywords: Technology: general issues; laser etching; water jet; polycrystalline silicon; orthogonal test; physical conditions; electrodeposition; SiC whisker; texture; morphology; self-healing; epoxy resin; microcapsule; insulating composite; breakdown strength; physical damage; electrical tree; analytical model; fabrics; weave pattern; shear deformation; tension-shear coupling; RTM; composites; FEM simulation; permeability characterization; design optimization; solar vehicles; photovoltaic roof; lightweight structures; carbon fiber-reinforced plastic (CFRP); natural frequencies; stiffness; heat exchange; Ansys ACP; constructal design; resin flow; porous media; numerical simulation; filling time; composite ship; composite structure; glass fiber content; void volume; burn-off test; calcination test; composite laminates; nanofibers; fracture; polyvinylidene fluoride; polysulfone; CFRP laminate; thin composite panel; viscoelastic material; vibration response; damping; experimental modal analysis; slamming; damage; viscoelastic layer